Assessing models of concurrent substance use and sexual consent cues in mainstream films. Issue 3 (3rd April 2022) - Marcantonio, Tiffany L.; Willis, Malachi; Rhoads, Kelley E.; Hunt, Mary E.; Canan, Sasha; Jozkowski, Kristen N.
Abstract: Objective College students may not view sexual consent communication while under the influence of substances (i.e., alcohol and drugs) as problematic if media models the co-occurrence of these behaviors. The purpose of this study was to assess the types of consent cues used by characters who are and are not under the influence of substances in mainstream films. Method: Four researchers inductively analyzed popular mainstream films ( N  = 50). Films were assessed for substance use and consent communication cues. Results: Characters using substances were depicted using implicit verbal and explicit nonverbal consent cues more than characters who had not used substances. Conclusion: Films may perpetuate cultural narratives that substance use can be part of the consent process and that consent is communicated differently when people have used substances. Prevention programs could include media literacy to address misleading messages college students may internalize about substance use and sexual consent communication.